A Study for Dental Caries Risk Factors on Rural School Children in Kediri, Indonesia - Khafid, Mohammad; Rahmadillah, Azzahra (Acta Odontologica Indonesia, 2025)
Dental caries incidence rate is still increasing. Therefore, research is needed to analyse dental risk factors. This study aimed to analyse dental caries risk factors in Indonesian school children. The study used a cross-sectional design and was conducted between March and April 2023 at SDN Mojo 1 Kediri, with participants in the age group 10-12 years. The questionnaire consisted of four main parts, including personal identity, demographics, oral health knowledge, oral hygiene habits, and the habit of consuming cariogenic foods. The intraoral examination (DMFT and deft index) was conducted after the questionnaire had been completed. The data were analysed using the SPSS software program with descriptive statistics and Spearman's Rho correlation test to determine the bivariate analysis between all variables. Knowledge of oral health, the habit of consuming cariogenic food, and the habit of maintaining oral hygiene were associated with the DMFT and deft index (p 0.05). This study revealed that the risk factors for dental caries in primary and permanent teeth in Indonesian school children, especially in rural areas, are the knowledge of oral health, the habit of consuming cariogenic food, and the habit of maintaining oral hygiene. At the same time, gender was not associated with the caries severity index, both in primary and permanent teeth.